Retrograde Insertion of An Antegrade Intramedullary Femoral Nail for Treatment of A Pathological Femoral Shaft Fracture in A Patient with Metastatic Bone Disease - Kevin Kusuman; I Gede Eka Wiratnaya (Indonesian Journal of Global Health Research, 2024)
Pathological fractures of the femur due to metastatic bone disease are challenging to treat, requiring stabilization to improve patient quality of life. Intramedullary nailing is a common treatment method, typically performed in an antegrade manner. However, in cases where antegrade insertion is difficult, retrograde techniques may be considered. We report a case of a 68-year-old female with metastatic breast cancer, presenting with a pathological fracture of the femoral shaft. Due to a large proximal femoral lesion and limited access for traditional antegrade femoral nail insertion, a retrograde approach was chosen. A standard antegrade intramedullary femoral nail was inserted retrograde through the distal femur. The procedure was successful, providing immediate stability and pain relief. Postoperatively, the patient was able to ambulate with assistance and was discharged for further oncological management. The retrograde insertion of an antegrade femoral nail offers an alternative in cases where antegrade insertion is not feasible due to proximal femoral involvement. While antegrade nailing is traditionally preferred, retrograde techniques offer comparable stability and functional outcomes, especially in metastatic bone disease where palliative treatment is a priority. This approach allows for reduced surgical trauma and faster recovery. Retrograde insertion of an antegrade femoral nail can be a viable option for stabilizing pathological femoral shaft fractures in patients with metastatic bone disease. It provides a feasible alternative when conventional approaches are not suitable, improving patient outcomes and quality of life.